x(2x+7)=

Simple and best practice solution for x(2x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2x+7)= equation:


Simplifying
x(2x + 7) = 0

Reorder the terms:
x(7 + 2x) = 0
(7 * x + 2x * x) = 0
(7x + 2x2) = 0

Solving
7x + 2x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(7 + 2x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(7 + 2x)' equal to zero and attempt to solve: Simplifying 7 + 2x = 0 Solving 7 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 0 + -7 2x = 0 + -7 Combine like terms: 0 + -7 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5

Solution

x = {0, -3.5}

See similar equations:

| 11-8b=-5-4b | | 4a+12=-16 | | 4(y-4)=2(y+25)-4 | | 10x-18=x+63 | | 5Y+9=8Y-6 | | -8+9n=10 | | 7m-6=-104 | | 7x+60=x+60 | | (4x^2+4x+1)-(4x^2+2)=8x+16 | | 3-(5x-1)/10=(x-1)/5-(x-3)/2 | | 5r=-1 | | 5r=-2 | | 7-6a=1-4a+a | | 4u+13=65 | | 4p-4=56 | | 9x-90=4x+55 | | A=49sqin | | 5(x-5)+5=-50 | | 6b+3=4b+5 | | 4/k=6=11 | | f(x)=6x^2+5x+3 | | 21/3x5-11= | | 1/(2sqrtx)=0.1111111111 | | -3(2x+6)-4+5x=4(x-5)+9-2x | | 3(x-3)-20=-23 | | -n-1/6=5 | | 200+3x=2+5x | | (9x+20)+(7x+x)=180 | | 5(2x+4)=70 | | 1/2x6= | | -14=a+5 | | 28=8+2n |

Equations solver categories